UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI MODEL PEMBELAJARAN LANGSUNG SISWA KELAS I SD NEGERI 001 UKUI SATU - ', Nurhamimah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low results of social studies students of class I SD Negeri001 Ukui Satu. Of the 20 students only 10 students who completed study results. This studyaims to improve learning outcomes IPS through direct learning model application. Thisresearch is a class act, carried out by two cycles. Data of this research focuses on improvingstudent learning outcomes IPS. IPS expressed increasing learning outcomes based on initialscore of student learning outcomes by 65 to 50% the percentage of completeness, the firstcycle increased with the acquisition of learning outcomes at 69.25 with the percentage ofcompleteness 70%. And the second cycle learning outcomes increased with the acquisition of74.5 to 85% the percentage of completeness. Based on this it can be concluded that theapplication of direct learning model can improve student learning outcomes IPS 001 firstgrade of SD Negeri 001 Ukui Satu.